MONETARY POLICY MANAGES TO STABILISE THE INDONESIAN ECONOMY: ANALYSING USING THE ARDL AND NARDL APPROACHES - Abdul Hayy Haziq, Mohamad; Rossazana, Ab Rahim; PUTRA, PAMUNGKAS (Seybold Publication, 2024)
Throughout its history, Indonesia, a developing country and a member of the Association of Southeast Asian Nations, has encountered numerous economic issues. After the hyperinflation crisis between 1997 and late 1998, the Indonesian economy has been growing slowly. However, strong monetary policy fundamentals, such as interest rate increases and money value stabilization, can be useful tools for combating hyperinflation and regaining economic stability. Therefore, this study focuses on the impact of monetary policies on inflation in Indonesia, examining the components of interest rate, lending interest rate, and total reserves as independent variables. The observation was conducted for a period of 37 years from 1986 to 2022, and the analyses are conducted using the autoregressive distributed lag and nonlinear autoregressive distributed lag approaches. The results show that during Indonesia’s 1997 hyperinflation crisis, money creation was lowered. The Central Bank of Indonesia realized that most people could not afford to pay off their debts; hence, it limited the amount of loans it issued to the private sector. Raising interest rates substantially affected the value of money and the amount of market liquidity. This study also indicates that the Central Bank of Indonesia is mature enough to understand the economic crisis and make the right decision, as per classical monetary theory.